European development policies towards African, Caribbean and Pacific countries: from Lomé to Economic Partnership Agreements - Oster, Marina (Department of Commercial Law, 2014)
This paper aims to examine and evaluate the relationship between the EU and ACP countries from the Lomé Conventions to the current Cotonou Agreement, and, in particular, the new Economic Partnership Agreements which will affect the ACP countries by far more than the European Union. This paper is structured as following: At first, a short overview about the development of the trade relations between the European Community and later on the European Union and the ACP-countries will be shown. Further on, the main reasons for the changed development policy will be shown as well as the success of the Lomé era will be evaluated. In the fourth and fifth part the current situation of the trade negotiations, i. e. trade relations under the Cotonou Agreement, and the future Economic Partnership Agreements as well as their expected impact on the ACPs seen from the different perspectives views and expectations expressed by the European Union on the one hand, and by the Non-Governmental-Organizations (NGOs) and the ACP countries on the other hand - will be examined and evaluated as far as possible at the moment.